Cytoreductive surgery and intraperitoneal chemotherapy versus systemic chemotherapy for colorectal peritoneal metastases: A randomised trial. (January 2016) - Cashin, P.H.; Mahteme, H.; Spång, N.; Syk, I.; Frödin, J.E.; Torkzad, M.; Glimelius, B.; Graf, W.
Abstract: Background: First-line treatment of isolated resectable colorectal peritoneal metastases remains unclear. This study (the Swedish peritoneal study) compares cytoreductive surgery and intraperitoneal chemotherapy (surgery arm) with systemic chemotherapy (chemotherapy arm). Methods: Patients deemed resectable preoperatively were randomised to surgery and intraperitoneal 5-fluorouracil 550 mg/m 2 /d for 6 d with repeated courses every month or to systemic oxaliplatin and 5-fluorouracil regimen every second week. Both treatments continued for 6 months. Primary end-point was overall survival (OS) and secondary end-points were progression-free survival (PFS), and morbidity. Results: The study terminated prematurely when 48 eligible patients (24/arm) were included due to recruitment difficulties. Two-year OS was 54% in the surgery arm and 38% in the chemotherapy arm ( p  = 0.04). After 5 years, 8 versus 1 patient were alive, respectively ( p  = 0.02). Median OS was 25 months versus 18 months, respectively, hazard ratio 0.51 (95% confidence interval: 0.27–0.96, p  = 0.04). PFS in the surgery arm was 12 months versus 11 months in the chemotherapy arm ( p  = 0.16) with 17% versus 0% 5-year PFS. Grade III–IV morbidity was seen in 42% and 50% of the patients, respectively. No mortalities. Conclusions: Cytoreductive surgery with intraperitoneal chemotherapy may be superior to systemic oxaliplatin-based treatment of colorectal cancer with resectable isolated peritoneal metastases.(ClinicalTrials.gov nr:NCT01524094 ). Highlights: We examine two treatment options for patients with colorectal peritoneal metastases. Cytoreductive surgery and intraperitoneal chemotherapy versus systemic chemotherapy. Our end-points were overall survival, progress-free survival and morbidity. Cytoreductive surgery with postoperative intraperitoneal chemotherapy was superior.